Curación de contenidos y praxis pedagógica : un modelo de formación para el profesorado universitario (Praxis Educativa, 2026)
The research addresses the need to develop digital competencies in university professors to adopt more active and engaging pedagogies. In this regard, the study focuses on creating a pedagogical model that facilitates training in content curation. To develop the model, a systemic, structural, and functional approach was used in defining its subsystems and components, complemented by a literature review that established the epistemic foundations of the proposal. The model integrates three subsystems that promote training in content curation, the use of digital tools, and didactics. Moreover, the interaction between the components reveals new theoretical relationships and a higher-level integrative quality that demonstrates the teacher's comprehensive training. It is concluded that this model can strengthen didactic performance and support continuous training in the current educational context.
Keywords: Digital skills; Teaching practice; Educational models; Training; Teaching materials